PERANCANGAN MODEL CRITICAL SUCCESS FACTOR PADA IMPLEMENTASI MANAJEMEN KUALITAS PROYEK KONSTRUKSI DI PT REKAYASA INDUSTRI - Husniyatika, Nada
PT Rekayasa Industri is one of the company that specializes in construction which was established back in 1981. Currently, the company has handled more than 130 projects regarding factory constructions. One of the values that this company has is customer-focus. This value is realized by paying attention to the quality of every project carried out by the company using project quality management process that refers to ISO9001. But, the implementation is seen as ineffective. There hasn’t been a significant effort by the company to acknowledge factors that causes the ineffectiveness of project quality management process. Therefore, it is necessary to establish a Critical Success Factor (CSF) on the project quality management process so that the process can be done effectively according to the objective. The designing of initial Critical Success Factor model was carried out by literature study and thorough discussion with PT Rekayasa Industri’s Project Quality Manager. Initial CSF model consists of 9 CSF groups and 24 CFS items which then validated by experts by using Content Validity Ratio (CVR). Validation results show that there is an increase in 6 CSF item and sentence corrections on 2 CSF items so that the final CSF model consists of 9 groups and 30 items. Furthermore, the creation of contextual relationships was carried out to all groups with Interpretive Structural Modelling (ISM) method, followed by group classifications using MICMAC (Matrice d' Impacts Croisés-Multiplication Appliquée á un Classement). The relationship was determined by having discussion with PT Rekayasa Industri’s Project Quality Manager. Next, the contextual model was validated by distributing questionnaires to 25 project managers using PLS-SEM method. From the validation result, it is found that the model qualifies as satisfactory by eliminating 5 CSF items. The final model that has been statistically tested consists of 9 CSF groups and 25 CSF items. The findings of this research show that there are two main factors that are key to the implementation of project quality management in PT Rekayasa Industri, which are top management’s commitment and employees’ support and cooperation. Keyword: construction, construction project, quality, project quality management, Critical Success Factor, Interpretive Structural Modeling, PLS-SEM